Sharia Economic Dispute Resolution Model According to Qanun No. 11 of 2018 concerning Sharia Financial Institutions - Syamsul Rizal; Cut Dara; Muammar Khadafi; Kafrawi Kafrawi; Husnaini Husnaini; zulhamdi zulhamdi (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
When many business entity activities start to appear that use the sharia label, the resolution must be carried out by institutions that truly understand sharia economics. So, creating economic products that have the term sharia attached to them is not easy and requires various kinds of adjustments, such as; applicable laws and regulations, contemporary economic developments in global society which tend to be value-free, varied transaction models, and so on. All of this must be able to be adjusted to sharia principles. The problem formulation in this research is: What is the Sharia Economic Dispute Resolution Model seen from Qanun No. 11 of 2018 concerning Sharia Financial Institutions? The type of research used is library research, namely by studying and examining sources. written text that is relevant to the discussion material. The results of this research are a model for Sharia Economic Dispute Resolution after the implementation of Qanun No. 11 of 2018 concerning Sharia Financial Institutions, a model for resolving disputes through non-litigation (outside of court), namely a model for resolving disputes that is carried out using methods that exist outside of court. usually called an alternative dispute resolution institution.